Sensorimotor Inhibition and Mobility in Genetic Subgroups of Parkinson's Disease - Martini, Douglas N.; Morris, Rosie; Kelly, Valerie E.; Hiller, Amie; Chung, Kathryn A.; Hu, Shu-Ching; Zabetian, Cyrus P.; Oakley, John; Poston, Kathleen; Mata, Ignacio F.; Edwards, Karen L.; Lapidus, Jodi A.; et al. (Frontiers in Neurology, 2020)
Background: Mobility and sensorimotor inhibition impairments are heterogeneous in Parkinson’s disease (PD). Genetics may contribute to this heterogeneity since the apolipoprotein (APOE) ε4 allele and glucocerebrosidase (GBA) gene variants have been related to mobility impairments in otherwise healthy older adult (OA) and PD cohorts. The purpose of this study is to determine if APOE or GBA genetic status affects sensorimotor inhibition and whether the relationship between sensorimotor inhibition and mobility differs in genetic sub-groups of PD. Methods: 93 participants with idiopathic PD (53 non-carriers; 23 ε4 carriers; 17 GBA variants) and 72 OA (45 non-carriers; 27 ε4 carriers) had sensorimotor inhibition characterized by short-latency afferent inhibition. Mobility was assessed in four gait domains (pace/turning, rhythm, trunk, variability) and two postural sway domains (area/jerkiness and velocity) using inertial sensors. Results: Sensorimotor inhibition was worse in the PD than OA group, with no effect of genetic status. Gait pace/turning was slower and variability was higher (p<0.01) in PD compared to OA. Postural sway area/jerkiness (p<0.01) and velocity (p<0.01) were also worse in the PD than OA group. Genetic status was not significantly related to any gait or postural sway domain. Sensorimotor inhibition was significantly correlated with gait variability (r=0.27; p=0.02) and trunk movement (r=0.23; p=0.045) in the PD group. In PD non-carriers, sensorimotor inhibition related to variability (r=0.35; p=0.010) and trunk movement (r=0.31; p=0.025). In the PD ε4 group, sensorimotor inhibition only related to rhythm (r=0.47; p=0.024), while sensorimotor inhibition related to pace/turning (r=-0.49; p=0.046) and rhythm (r=0.59; p=0.013) in the PD GBA group. Sensorimotor inhibition was significantly correlated with gait pace/turning (r=-0.27; p=0.04) in the OA group. There was no relationship between sensorimotor inhibition and postural sway. Conclusion: ε4 and GBA genetic status did not affect sensorimotor inhibition or mobility impairments in this PD cohort. However, worse sensorimotor inhibition was associated with gait variability in PD non-carriers, but with gait rhythm in PD ε4 carriers and with gait rhythm and pace in PD with GBA variants. Impaired sensorimotor inhibition had a larger effect on mobility in people with PD than OA and affected different domains of mobility depending on genetic status.